Twilight of the American State An Essay - SCHLAG, PIERRE (University of Michigan Press, 2023)
The sudden emergence of the Trump nation surprised nearly everyone, including journalists, pundits, political consultants, and academics. When Trump won in 2016, his ascendancy was widely viewed as a fluke. Yet time showed it was instead the rise of a movement-angry, militant, revanchist, and unabashedly authoritarian. How did this happen? Twilight of the American State offers a sweeping exploration of how law and legal institutions helped prepare the grounds for this rebellious movement. The controversial argument is that, viewed as a legal matter, the American state is not just a liberal democracy, as most Americans believe. Rather, the American state is composed of an uneasy and unstable combination of different versions of the state-liberal democratic, administered, neoliberal, and dissociative. Each of these versions arose through its own law and legal institutions. Each emerged at different times historically. Each was prompted by deficits in the prior versions. Each has survived displacement by succeeding versions. All remain active in the contemporary moment-creating the political-legal dysfunction America confronts today. Pierre Schlag maps out a big picture view of the tribulations of the American state. The book abjures conventional academic frameworks, sets aside prescriptions for quick fixes, dispenses with lamentations about polarization, and bypasses historical celebrations of the American Spirit.